Comparison of physical and mechanical properties of civil construction plaster and recycled waste gypsum from São Paulo, Brazil. (March 2019) - Cordon, Heloísa Cristina Fernandes; Cagnoni, Felipe Carvalho; Ferreira, Fabio Furlan
Abstract: This paper describes the physical and mechanical properties of powdered, paste and hardened materials obtained by recycling plaster waste collected at civil works. Recycling of waste generated in all sectors of society has become increasingly important for environment protection. Since gypsum waste has the same chemical composition of the rock that gives rise to the hemihydrate form after calcination at moderate temperatures (~ 150 °C), recycling becomes attractive by simply calcining the residue to generate a new hemihydrate. The objective of the reported work is to compare recycled gypsum waste to commercial plaster, as well as comparing a mixture of waste with commercial plaster. Both apparent bulk density and bulk density decreased with increasing content of recycled plaster in the mixture, while the setting time, water content to normal consistency and compressive strength all increased. The recycled plaster alone could be considered satisfactory for this kind of application, with no need for blending it with the commercial one. Furthermore, TGA and XRPD quantitative phase analysis by using the Rietveld method indicated that the microstructure of the recycled material presented no differences from the original one, which demonstrates the viability of this recycling process. Highlights: Physical properties of recycled plaster were better than the commercial material. Commercial plaster presented a high level of impurities, like dolomite. Recycled plaster particles and apparent bulk density are smaller than the commercial sample. Microstructure of the recycled material similar to the original one.